2021
DOI: 10.1186/s40712-021-00135-5
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural and mechanical studies of feedstock material in continuous extrusion process

Abstract: The challenge encountered in continuous forming process is the variation in mechanical strength of product formed with respect to process variables like extrusion wheel speed and diameter of product. In this research article, the micro-structural investigation of the aluminum (AA1100) feedstock material of 9.5-mm diameter has been carried out at various extrusion wheel speeds and diameter of product before and after deformation on commercial continuous extrusion setup TBJ350. The mechanical properties like yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Te consequence temperature of feedstock in CEP was investigated in order to determine the optimum torque and load needed to extrude the material of feedstock thru the die orifce. Te efects of CEP input parameters on extrudate microstructural and mechanical properties were investigated [17]. Te mechanical belongings of continuously extruded rod of feedstock aluminum alloy, for instance, hardness and ultimate tensile strength, were optimized by optimizing process variables such as speed of wheel and ratio of extrusion [18].…”
Section: Introductionmentioning
confidence: 99%
“…Te consequence temperature of feedstock in CEP was investigated in order to determine the optimum torque and load needed to extrude the material of feedstock thru the die orifce. Te efects of CEP input parameters on extrudate microstructural and mechanical properties were investigated [17]. Te mechanical belongings of continuously extruded rod of feedstock aluminum alloy, for instance, hardness and ultimate tensile strength, were optimized by optimizing process variables such as speed of wheel and ratio of extrusion [18].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the authors indicated that the product's quality was obtained by a combined optimization of wheel speed and the extrusion ratio. 12,13 A method based on the Bezier formulation mathematical model is used for manufacturing vortex extrusion dies and analysing the effect of various processing parameters on strain distribution and process load. The authors investigated the effective strain rate, stress, and temperature, which were predicted by the numerical simulation analysis.…”
Section: Introductionmentioning
confidence: 99%
“…This process needs no extra heating, thus saving energy. In addition, products with unlimited length can be manufactured, and the material utilization rate can reach more than 95% [2][3][4]. Therefore, continuous extrusion has been extensively applied for nonferrous alloys such as AM60 Mg [5], Al−Mg−Si [6], Cu−Te [7], Al−Fe−Cu [8], and Al−13Si−7.5Cu−Mg [9].…”
Section: Introductionmentioning
confidence: 99%